High cadence optical transient searches using drift scan imaging II: Event rate upper limits on optical transients of duration <21 ms and magnitude <6.6. (18th January 2021) - Tingay, Steven; Joubert, Wynand
Abstract: We have realised a simple prototype system to perform searches for short timescale optical transients, utilising the novel drift scan imaging technique described by Tingay (2020 ). We used two coordinated and aligned cameras, with an overlap field of view of approximately 3.7 deg $^2$, to capture over $34\, 000 × 5$ second images during approximately 24 h of observing. The system is sensitive to optical transients, due to an effective exposure time per pixel of 21 ms, brighter than a V magnitude of 6.6. In our 89.7 deg $^2$ h of observations, we find no candidate astronomical transients, giving an upper limit to the rate of these transients of 0.8 per deg $^2$ per day, competitive with other experiments of this type. The system is triggered by reflections from satellites and various instrumental effects, which are easily identifiable due to the two camera system. The next step in the development of this promising technique is to move to a system with larger apertures and wider fields of view.